Galectin-3 Negatively Regulates Hippocampus-Dependent Memory Formation through Inhibition of Integrin Signaling and Galectin-3 Phosphorylation - Chen, Yan-Chu; Ma, Yun-Li; Lin, Cheng-Hsiung; Cheng, Sin-Jhong; Hsu, Wei-Lun; Lee, Eminy H.-Y. (Frontiers in Molecular Neuroscience, 2017)
Galectin-3 is a member of the galectin protein family that was found to regulate cell proliferation, inhibit apoptosis and promotes inflammatory responses. Galectin-3 is also expressed in the adult rat hippocampus, but its role in learning and memory function is not known. Here, we find that contextual fear-conditioning training, spatial training and NMDA injection to rat CA1 area all dramatically decrease the level of endogenous galectin-3 expression. Overexpression of galectin-3 impairs fear memory, whereas fear retention, spatial memory and hippocampal long-term potentiation are enhanced in galectin-3 knockout mice. Further, galectin-3 is associated with integrin-alpha3 and this association is decreased after fear conditioning training. Transfection of galectin-3 siRNA to rat CA1 area facilitates fear memory and increases the phosphorylation level of FAK, but these effects were blocked by co-transfection of the FAK phosphorylation mutant Flag-FAKY397F. Further, the phospho-Ser level of galectin-3 is decreased by fear conditioning training. In addition, blockade of galectin-3 phosphorylation at Ser-6 facilitates fear memory whereas constitutive activation of galectin-3 at Ser-6 impairs fear memory. Galectin-1 plays a similar role in fear memory formation as galectin-3 does. Here, we first demonstrated that galectin-3 is a novel negative regulator of memory formation and it negatively regulates memory through both extracellular and intracellular mechanisms.